HUBUNGAN GAYA KEPEMIMPINAN SITUASIONAL DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN (Studi Kasus PT. Riau Pos Intermedia) - Farma "; Seno Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This study aims to determine the relationship of situational leadership styleand working environment on the performance of the employee (Case Study at PT.Riau Pos Intermedia. Styles situational leadership as a variable (X1), the workenvironment as a variable (X2) and employee performance as (Y).The method in this research is descriptive and quantitative using SPSS 20,wherein the samples used are permanent employees at PT. Riau Pos intermedia byrespondents as many as 59 people. The formula used to determine the sampleslovin, as well as a sampling technique by means of probability sampling includesimple random sampling. Data collection through questionnairesResults of analysis using multiple linear regression, t test and f test so thatit can be seen that the variable situational leadership style positive effect on theperformance of employees, the working environment have a significant effect onemployee performance, and significant relationship between the situationalleadership style and work environment on employee performance.Keywords: Situational Leadership Style, Work Environment, EmployeePerformance